Perovskite thin film, preparation method and application thereof

CN122995498APending Publication Date: 2026-10-27MINJIANG UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611119689.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

这些缺陷会在带隙中引入深能级陷阱态,显著增强载流子的非辐射复合,造成开路电压损失、填充因子下降及短路电流降低,直接制约器件效率的进一步提升

Benefits of technology

[0009]本发明的有益效果在于:本发明以4-溴-2-噻吩羧酸作为小分子添加剂制备钙钛矿光活性层,即钙钛矿薄膜;其分子结构中含有羧基(-COOH)、溴原子(-Br)及噻吩杂环三个功能性官能团,能够同时实现结晶调控、阴阳离子双重缺陷钝化和能级优化,从而显著提升钙钛矿太阳能电池的光电转换效率和长期稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995498A_ABST
    Figure CN122995498A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of solar cells, in particular to a perovskite thin film and a preparation method and application thereof. The small-molecule additive is 4-bromo-2-thiophene carboxylic acid, the 4-bromo-2-thiophene carboxylic acid is added into a perovskite precursor solution, and a perovskite thin film is prepared. The perovskite photoactive layer, i.e. the perovskite thin film, is prepared by taking 4-bromo-2-thiophene carboxylic acid as a small-molecule additive; the molecular structure contains three functional functional groups of a carboxyl group (-COOH), a bromine atom (-Br) and a thiophene heterocycle, can simultaneously realize crystallization regulation, anion and cation double-defect passivation and energy level optimization, and can significantly improve the photoelectric conversion efficiency and long-term stability of a perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell technology, specifically to a perovskite thin film, its preparation method, and its application. Background Technology

[0002] In recent years, organic-inorganic hybrid perovskite solar cells (PSCs) have made breakthrough progress in the photovoltaic field due to their outstanding advantages such as high light absorption coefficient, long carrier diffusion length, tunable bandgap, and low-temperature solution processing.

[0003] The photoelectric performance of perovskite solar cells is highly dependent on the crystal quality and defect density of the photoactive layer. While widely used low-temperature fabrication processes such as spin coating and blade coating offer advantages like simplicity and low cost, they are prone to problems such as disordered nucleation, uncontrolled growth, and chaotic grain orientation during rapid crystallization. This results in numerous structural defects within the film, including grain boundaries, vacancies, interstitial atoms, and uncoordinated ions. In lead-based perovskite systems, the most common defect type includes uncoordinated Pb. 2+ Defects include iodine vacancies, organic cation vacancies, and dangling bonds at grain boundaries. These defects introduce deep-level trap states into the band gap, significantly enhancing nonradiative recombination of charge carriers. This results in open-circuit voltage loss, a decrease in fill factor, and a reduction in short-circuit current, directly limiting further improvements in device efficiency. Simultaneously, defect sites exacerbate ion migration, phase separation, and structural instability, causing rapid battery degradation under illumination, electric fields, and humid and hot environments.

[0004] To address these challenges, researchers have developed a series of optimization strategies. Among them, Chinese invention patent CN119562746A discloses the use of 2-bromo-3-thiophenic acid as a small molecule additive to improve the performance of perovskite films. However, the photoelectric conversion efficiency of 2-bromo-3-thiophenic acid / high perovskite film is no more than 18%, which is far from the highest power conversion efficiency of titanium dioxide solar cells—25.7%. Summary of the Invention

[0005] The technical problem to be solved by this invention is: how to make perovskite solar cells have both high power conversion efficiency and low defects.

[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: a method for preparing perovskite thin films, wherein 4-bromo-2-thiophenic acid is added to a perovskite precursor solution to prepare a perovskite thin film.

[0007] Another technical solution adopted in this invention is: a perovskite thin film prepared by the above-mentioned method for preparing perovskite thin films, wherein the composition of the perovskite thin film is Cs. 0.05 FA 0.93MA 0.02 Pb(I 0.98 Br 0.02 3.

[0008] Another technical solution adopted in this invention is the application of the above-mentioned perovskite thin film in perovskite solar cells, characterized in that the perovskite solar cell comprises a transparent conductive substrate, a hole transport layer, a perovskite thin film, an electron transport layer, a buffer layer, and a metal electrode stacked sequentially.

[0009] The beneficial effects of this invention are as follows: This invention uses 4-bromo-2-thiophenic acid as a small molecule additive to prepare a perovskite photoactive layer, namely a perovskite thin film; its molecular structure contains three functional groups: carboxyl group (-COOH), bromine atom (-Br) and thiophene heterocycle, which can simultaneously achieve crystallization regulation, anion and cation dual defect passivation and energy level optimization, thereby significantly improving the photoelectric conversion efficiency and long-term stability of perovskite solar cells. Attached Figure Description

[0010] Figure 1 Here is the chemical structural formula of BTCA; Figure 2 The XRD patterns of the perovskite film of Comparative Example 1 (unmodified) and Example 1 (BTCA modified) are shown. Figure 3 The XRD patterns of perovskite thin films in Examples 1-3 and Comparative Example 1 are shown below. Figure 4 Here is a surface SEM image of the perovskite film in Comparative Example 1. Figure 5 Here is a surface SEM image of the perovskite thin film of Example 1; Figure 6 The image shows a cross-sectional SEM image of the perovskite film in Comparative Example 1. Figure 7 Here is a cross-sectional SEM image of the perovskite thin film of Example 1; Figure 8 Steady-state PL spectra of Comparative Example 1 (unmodified) perovskite film and Example 1 (BTCA modified) perovskite film; Figure 9 TRPL decay curves of Comparative Example 1 (unmodified) perovskite film and Example 1 (BTCA modified) perovskite film; Figure 10 The JV curves are for the comparative example 1 (unmodified) solar cell and the example 1 (BTCA modified) perovskite solar cell. Figure 11 The IPCE spectra and integrated current curves are for the comparative example 1 (unmodified) solar cell and the example 1 (BTCA modified) perovskite solar cell. Detailed Implementation

[0011] To explain in detail the technical content, objectives, and effects of the present invention, the following description is provided in conjunction with the embodiments and accompanying drawings.

[0012] The abbreviations and their Chinese definitions in this article are shown in the table below.

[0013] abbreviation Chinese definition abbreviation Chinese definition FAI Formamidinium iodide BTCA 4-Bromo-2-thiophenic acid MABr Methylamine bromide XRD diffraction peaks X-ray diffraction peaks MACl Methylamine chloride Urbach Energy Urbach energy DMF N,N-Dimethylformamide BCP Bathing Copper Spirit DMSO dimethyl sulfoxide FTO Fluorine-doped tin oxide Me-4PACz [4-(3,6-Dimethyl-9H-carbazole-9-yl)butyl]trimethylammonium tetrafluoroborate PEACl Phenethyl ammonium chloride <![CDATA[PC 61 BM]]> [6,6]-Phenylated-C61-Butyrate Methyl Ester SAM Self-assembled monolayer SEM Scanning electron microscope JSC Short-circuit current density PL spectrum Photoluminescence spectrum VOC Open circuit voltage JV curve Current-voltage curve FF Fill factor IPCE spectroscopy Incident photon-electron conversion efficiency spectrum PCE Photoelectric conversion efficiency This invention is applicable to perovskite solar cell applications. By adding 4-bromo-2-thiophenic acid to the perovskite thin film, a perovskite solar cell with both high power conversion efficiency and low defects can be obtained.

[0014] A method for preparing a perovskite thin film involves adding 4-bromo-2-thiophenic acid to a perovskite precursor solution to obtain a perovskite thin film.

[0015] As can be seen from the above description, the beneficial effects of the present invention are as follows: The present invention uses BTCA as a small molecule additive to prepare perovskite thin films, which significantly improves the crystallinity of the perovskite thin films, enhances the intensity of XRD diffraction peaks, reduces the defect state density of the thin films, reduces the Urbach energy, extends the carrier lifetime, optimizes the energy level structure, and significantly reduces the energy level barrier with the electron transport layer; it has the advantages of simple preparation process, complete compatibility with existing solution methods, and low cost, which can significantly improve the photoelectric conversion efficiency and long-term stability of perovskite solar cells, and has good prospects for industrial application, and can be widely used in the large-scale production of perovskite solar cells.

[0016] The mechanism of action of BTCA in perovskite thin films is as follows: (1) The carboxyl group (-COOH) in the BTCA molecule acts as a Lewis base, forming a stable Pb-O coordination bond with the uncoordinated Pb2+ in the perovskite, effectively passivating deep energy level defects; (2) The size of the bromine atom (-Br) in the BTCA molecule is similar to that of the iodide ion, which can fill the iodine vacancies in the crystal lattice, inhibit ion migration and stabilize the crystal structure; (3) The carboxyl group and FA in the BTCA molecule + NH···O hydrogen bonds are formed to anchor organic cations; (4) The thiophene ring in the BTCA molecule has a π-conjugated structure, which helps to enhance the interfacial charge transport capability and reduce carrier recombination loss; (5) BTCA through Pb 2+ Coordination and FA + The dual anchoring effect of hydrogen bonds slows down the crystallization rate of perovskite, allowing for more complete crystal growth and the formation of large-sized columnar crystal structures that span the entire film thickness, thus reducing grain boundary defects.

[0017] Compared to 2-bromo-3-thiophenic acid, 4-bromo-2-thiophenic acid exhibits superior photoelectric conversion efficiency. Chemically, both carboxyl-containing molecules possess similar properties to FA. + The ability to form hydrogen bonds varies, but the different substitution positions lead to significant differences in actual effects. In 2-bromo-3-thiophenecarboxylic acid, the bromine atom is located adjacent to the carboxyl group, and its large steric hindrance shields the carbonyl oxygen in the carboxyl group from reacting with FA. + The proximity of the bromine atom to the carboxyl group severely weakens the hydrogen bond anchoring ability; while the bromine atom of 4-bromo-2-thiophenecarboxylic acid is located in the meta position far from the carboxyl group, allowing the carboxyl group to extend freely and the -C=O group to be fully exposed. Therefore, it can efficiently form NH···O hydrogen bonds, achieving effective anchoring of FA. + Stable anchoring; that is, 2-bromo-3-thiophenic acid is anchored only through Pb 2+ Passivation is achieved through coordination and iodine vacancies; 4-bromo-2-thiophenic acid is passed through Pb. 2+ Coordination, iodine vacancy filling and FA + Hydrogen bond anchoring is used for triple passivation, which induces the formation of a large columnar crystal structure that runs through the entire film thickness, which can significantly improve photoelectric conversion efficiency.

[0018] Furthermore, 4-bromo-2-thiophenic acid was added to the perovskite precursor solution and dissolved, then spin-coated and annealed to obtain a thin film; subsequently, PEACl solution was spin-coated onto the thin film, and annealed again to obtain a perovskite thin film.

[0019] Furthermore, the perovskite precursor solution is prepared by dissolving PbI2, PbBr2, FAI, CsI, MABr and MACl in a mixed solvent to obtain the perovskite precursor solution.

[0020] Furthermore, the mixed solvent includes DMF and DMSO in a volume ratio of 3 to 5:1.

[0021] As can be seen from the above description, changes in the volume ratio of the mixed solvent can affect the crystallinity of perovskite films.

[0022] Furthermore, the specific steps of spin coating are as follows: first spin coating at 800~1200 rpm for 8~12s, then accelerate to 3800~4200 rpm for 38~42s, and add the anti-solvent 3~8s before the end of spin coating.

[0023] Further, 4-bromo-2-thiophenic acid was added to the perovskite precursor solution and dissolved, then spin-coated and annealed at 90~100℃ to obtain a thin film; subsequently, PEACl solution was spin-coated onto the thin film and annealed at 95~105℃ to obtain a perovskite thin film.

[0024] As can be seen from the above description, in the perovskite thin film preparation process, the first annealing is to evaporate the precursor solvent to obtain the perovskite thin film; the second annealing is to remove the PEACl solvent, thereby passivating the perovskite thin film and improving its crystallinity.

[0025] Furthermore, the amount of 4-bromo-2-thiophenic acid added to the perovskite precursor solution is 0.05~0.5 mg / mL.

[0026] Preferably, the amount of 4-bromo-2-thiophenic acid added to the perovskite precursor solution is 0.1 mg / mL.

[0027] As can be seen from the above description, the crystallinity of perovskite films first increases and then decreases with the change in the amount of 4-bromo-2-thiophenecarboxylic acid added.

[0028] Another technical solution adopted in this invention is: a perovskite thin film prepared by the above-mentioned method for preparing perovskite thin films, wherein the composition of the perovskite thin film is Cs. 0.05 FA 0.93 MA 0.02 Pb(I 0.98 Br 0.02 3.

[0029] As can be seen from the above description, the amount of PbI2, PbBr2, FAI, CsI, MABr, and MACl added is unlimited, and any combination that can form CsI can be used. 0.05 FA 0.93 MA 0.02 Pb(I 0.98 Br 0.02 Any amount of 3 can be added.

[0030] Another technical solution adopted in this invention is: the application of the above-mentioned perovskite thin film in perovskite solar cells, wherein the perovskite solar cell comprises a transparent conductive substrate, a hole transport layer, a perovskite thin film, an electron transport layer, a buffer layer and a metal electrode stacked in sequence.

[0031] As can be seen from the above description, the final structure obtained by this invention is FTO / Me-4PACz / BTCA modified perovskite / PC. 61 An inverted perovskite solar cell with BM / BCP / Ag structure; the photoelectric conversion efficiency of this perovskite solar cell reaches 25.2%, the open-circuit voltage reaches 1.19V, and the fill factor reaches 83.1%.

[0032] Furthermore, the hole transport layer material can be any existing perovskite solar cell hole transport layer material, such as Me-4PACz self-assembled monolayer.

[0033] Furthermore, the hole transport layer is prepared by spin-coating a Me-4PACz solution onto a transparent conductive substrate, followed by annealing and cleaning to obtain the hole transport layer.

[0034] As can be seen from the above description, annealing is used to evaporate the solvent during the preparation of the hole transport layer, which promotes the self-assembly of Me-4PACz to obtain a dense hole transport layer.

[0035] Furthermore, the electron transport layer material can be any existing perovskite solar cell electron transport layer material, such as PC. 61 BM.

[0036] Furthermore, the method for fabricating the electron transport layer is as follows: PC 61 BM solution was spin-coated onto a perovskite thin film to obtain an electron transport layer.

[0037] Furthermore, the buffer layer material can be any existing perovskite solar cell buffer layer material, such as BCP.

[0038] Furthermore, the metal electrode can be any existing perovskite solar cell metal electrode, such as a silver electrode.

[0039] Example 1 of the present invention is a method for preparing a perovskite solar cell, the specific steps of which are as follows: S1: The pre-etched FTO conductive glass is ultrasonically cleaned with deionized water, acetone and anhydrous ethanol for 15 minutes in sequence. After being dried with nitrogen, it is placed in an ultraviolet ozone cleaner for 15 minutes to remove residual organic pollutants on the surface. S2: The Me-4PACz solution (isopropanol as solvent, 0.5 mg / mL) was spin-coated onto the S1-treated FTO conductive glass at 4000 rpm for 30 s, followed by annealing at 100 °C for 10 min. After annealing, the sample was cleaned by spin coating with isopropanol at 5000 rpm for 30 seconds to remove unbound SAM molecules and residual solvent. Then, it was annealed at 100°C for 10 minutes to obtain the hole transport layer. S3: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), 760.7 mg PbI2, 11.0 mg PbBr2, 239.9 mg FAI, 19.5 mg CsI, 3.4 mg MABr and 6.75 mg MACl were dissolved in 1 mL of mixed solvent (DMF:DMSO = 4:1, v / v) to obtain a perovskite precursor solution; 0.1 mg / mL BTCA was added to the perovskite precursor solution and stirred at 40 °C for 30 min until completely dissolved to obtain a BTCA-modified perovskite precursor solution. S4: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), the BTCA-modified perovskite precursor solution was deposited onto the hole transport layer using a one-step spin-coating method. The spin-coating procedure was as follows: spin-coating at 1000 rpm for 10 s, then accelerating to 4000 rpm for 40 s. 5 s before the end of the spin-coating, 180 μL of chlorobenzene was added as an anti-solvent. After spin-coating, the film was annealed at 95℃ for 60 min to obtain the thin film. Subsequently, a PEACl solution (1 mg / mL) was spin-coated onto the film and annealed at 100℃ for 10 min to obtain the perovskite thin film. The composition of the perovskite thin film was Cs. 0.05 FA 0.93 MA 0.02 Pb(I 0.98 Br 0.02 3; S5: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), place PC... 61 BM solution (chlorobenzene as solvent, 20 mg / mL) was spin-coated onto the perovskite film at 4000 rpm for 30 s to obtain an electron transport layer. S6: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), spin-coat the BCP solution (isopropanol as solvent, 0.5 mg / mL) onto the electron transport layer at a speed of 4500 rpm for 60 s as a buffer layer. S7: Under high vacuum conditions (5 10 -4 pa) deposited a 100 nm thick silver electrode by thermal evaporation.

[0040] Embodiment 2 of the present invention is The only difference between Example 2 and Example 1 is that the amount of BTCA added in S3 is 0.05 mg / mL.

[0041] Embodiment 3 of the present invention is The only difference between Example 3 and Example 1 is that the concentration of BTCA added in S3 is 0.5 mg / mL.

[0042] Comparative Example 1 of the present invention is The only difference between Comparative Example 1 and Example 1 is that BTCA is not added in S3 as a blank control device.

[0043] Performance testing The photoelectric performance of the perovskite solar cells prepared in Examples 1-3 and Comparative Example 1 was tested under the following conditions: 25°C, standard AM 1.5G illumination, and illuminance of 100 mW / cm². 2JV curve tests were conducted using the Enlitech SS-F5-3A solar simulator. The test results are shown below. Figure 1-11 .

[0044] in Figure 1 The image shows the molecular structure of 4-bromo-2-thiophenic acid, revealing its relatively small steric hindrance. Figure 2 It can be seen that the diffraction peak intensities of the perovskite film were all improved after BTCA modification, indicating that BTCA modification improved its crystallinity. Figure 3 As can be seen, with the increase of BTCA addition, the crystallinity of the perovskite film first increases and then decreases, with 0.1 mg / ml being the optimal addition amount. Figure 4-7 It can be seen that after BTCA modification, the perovskite film has a significantly increased particle size and a significantly improved crystallinity. Figure 8-9 It can be seen that nonradiative recombination is effectively suppressed in the perovskite thin film modified with BTCA, and the carrier lifetime is significantly extended. Figure 10-11 It can be seen that the device modified with BTCA has superior optoelectronic performance, including higher photoelectric conversion efficiency and integrated current density.

[0045] The optimal device performance for Example 1 (BTCA 0.1 mg / mL) is: J SC = 25.2 mA / cm 2 V OC = 1.185 V, FF = 83.1%, PCE = 25.21%; the device performance of Example 2 (BTCA 0.05 mg / mL) was slightly lower than that of Example 1, but still significantly better than that of Comparative Example 1; the device performance of Example 3 (BTCA 0.5 mg / mL) was lower than that of Example 1, indicating that there is an optimal range for BTCA addition. The optimal device performance of Comparative Example 1 is: J SC = 24.6 mA / cm 2 V OC = 1.150V, FF =80.5%, PCE = 22.94%.

[0046] The above results indicate that BTCA, as an additive, can significantly improve the photoelectric conversion efficiency of perovskite solar cells, with an optimal addition concentration of 0.1 mg / mL.

[0047] Example 4 of the present invention is a method for preparing a perovskite solar cell, the specific steps of which are as follows: S1: The pre-etched FTO conductive glass is ultrasonically cleaned with deionized water, acetone and anhydrous ethanol for 15 minutes in sequence. After being dried with nitrogen, it is placed in an ultraviolet ozone cleaner for 15 minutes to remove residual organic pollutants on the surface. S2: The Me-4PACz solution (isopropanol as solvent, 0.5 mg / mL) was spin-coated onto the S1-treated FTO conductive glass at 4000 rpm for 30 s, followed by annealing at 100 °C for 10 min. After annealing, the sample was cleaned by spin coating with isopropanol at 5000 rpm for 30 seconds to remove unbound SAM molecules and residual solvent. Then, it was annealed at 100°C for 10 minutes to obtain the hole transport layer. S3: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), 760.7 mg PbI2, 11.0 mg PbBr2, 239.9 mg FAI, 19.5 mg CsI, 3.4 mg MABr and 6.75 mg MACl were dissolved in 1 mL of mixed solvent (DMF:DMSO = 3:1, v / v) to obtain a perovskite precursor solution; Add 0.05 mg / mL BTCA to the perovskite precursor solution and stir at 40 °C for 30 min until completely dissolved to obtain a BTCA-modified perovskite precursor solution. S4: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), the BTCA-modified perovskite precursor solution was deposited onto the hole transport layer using a one-step spin-coating method. The spin-coating procedure was as follows: spin-coating at 800 rpm for 12 s, then accelerating to 3800 rpm for 42 s. 3 s before the end of the spin-coating, 180 μL of chlorobenzene was added as an anti-solvent. After spin-coating, the film was annealed at 90℃ for 60 min to obtain the thin film. Subsequently, a PEACl solution (1 mg / mL) was spin-coated onto the film and annealed at 95℃ for 10 min to obtain the perovskite thin film. The composition of the perovskite thin film was Cs. 0.05 FA 0.93 MA 0.02 Pb(I 0.98 Br 0.02 3; S5: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), place PC... 61 BM solution (chlorobenzene as solvent, 20 mg / mL) was spin-coated onto the perovskite film at 4000 rpm for 30 s to obtain an electron transport layer. S6: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), spin-coat the BCP solution (isopropanol as solvent, 0.5 mg / mL) onto the electron transport layer at a speed of 4500 rpm for 60 s as a buffer layer. S7: Under high vacuum conditions (5 10 -4pa) deposited a 100 nm thick silver electrode by thermal evaporation.

[0048] Example 5 of the present invention is a method for preparing a perovskite solar cell, the specific steps of which are as follows: S1: The pre-etched FTO conductive glass is ultrasonically cleaned with deionized water, acetone and anhydrous ethanol for 15 minutes in sequence. After being dried with nitrogen, it is placed in an ultraviolet ozone cleaner for 15 minutes to remove residual organic pollutants on the surface. S2: The Me-4PACz solution (isopropanol as solvent, 0.5 mg / mL) was spin-coated onto the S1-treated FTO conductive glass at 4000 rpm for 30 s, followed by annealing at 100 °C for 10 min. After annealing, the sample was cleaned by spin coating with isopropanol at 5000 rpm for 30 seconds to remove unbound SAM molecules and residual solvent. Then, it was annealed at 100°C for 10 minutes to obtain the hole transport layer. S3: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), 760.7 mg PbI2, 11.0 mg PbBr2, 239.9 mg FAI, 19.5 mg CsI, 3.4 mg MABr and 6.75 mg MACl were dissolved in 1 mL of mixed solvent (DMF:DMSO = 5:1, v / v) to obtain a perovskite precursor solution; Add 0.5 mg / mL BTCA to the perovskite precursor solution and stir at 40 °C for 30 min until completely dissolved to obtain a BTCA-modified perovskite precursor solution. S4: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), the BTCA-modified perovskite precursor solution was deposited onto the hole transport layer using a one-step spin-coating method. The spin-coating procedure was as follows: spin-coating at 1200 rpm for 8 s, then accelerating to 4200 rpm for 38 s, and adding 180 μL of chlorobenzene as an anti-solvent 8 s after the spin-coating was completed. After spin-coating, the film was annealed at 100℃ for 60 min to obtain the film. Subsequently, a PEACl solution (1 mg / mL) was spin-coated onto the film and annealed at 105℃ for 10 min to obtain the perovskite film. The composition of the perovskite film was Cs. 0.05 FA 0.93 MA 0.02 Pb(I 0.98 Br 0.02 3; S5: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), place PC... 61BM solution (chlorobenzene as solvent, 20 mg / mL) was spin-coated onto the perovskite film at 4000 rpm for 30 s to obtain an electron transport layer. S6: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), spin-coat the BCP solution (isopropanol as solvent, 0.5 mg / mL) onto the electron transport layer at a speed of 4500 rpm for 60 s as a buffer layer. S7: Under high vacuum conditions (5 10 -4 pa) deposited a 100 nm thick silver electrode by thermal evaporation.

[0049] Example 6 of the present invention is a method for preparing a perovskite thin film, the specific steps of which are as follows: In a vacuum glove box (H2O < 1 ppm, O2 < 1 ppm), 760.7 mg PbI2, 11.0 mg PbBr2, 239.9 mg FAI, 19.5 mg CsI, 3.4 mg MABr and 6.75 mg MACl were dissolved in 1 mL of a mixed solvent (DMF:DMSO = 4:1, v / v) to obtain a perovskite precursor solution. 0.1 mg / mL BTCA was added to the perovskite precursor solution and stirred at 40 °C for 30 min until completely dissolved to obtain a BTCA-modified perovskite precursor solution. A BTCA-modified perovskite precursor solution was deposited onto a hole transport layer using a one-step spin-coating method. The spin-coating procedure was as follows: spin-coating at 1000 rpm for 10 s, then accelerating to 4000 rpm for 40 s; 5 s before the end of spin-coating, 180 μL of chlorobenzene was added as an anti-solvent. After spin-coating, the film was annealed at 95 °C for 60 min to obtain a thin film. Subsequently, a PEACl solution (1 mg / mL) was spin-coated onto the film and annealed at 100 °C for 10 min to obtain a perovskite film with a composition of Cs. 0.05 FA 0.93 MA 0.02 Pb(I 0.98 Br 0.02 3.

[0050] Example 7 of the present invention is a perovskite thin film prepared by the preparation method of Example 5, wherein the composition of the perovskite thin film is Cs. 0.05 FA 0.93 MA 0.02 Pb(I 0.98 Br 0.02 3.

[0051] In summary, the perovskite thin film, its preparation method, and its applications provided by this invention have the following advantages: 1. This invention is the first to apply 4-bromo-2-thiophenecarboxylic acid (BTCA) as a multifunctional small molecule additive to perovskite solar cells. The BTCA molecule contains three functional groups: carboxyl group (-COOH), bromine atom (-Br) and thiophene ring. It can achieve multiple functions through a single molecule: carboxyl group coordination to passivate Pb2+ defects, bromine atom filling iodine vacancies, and thiophene ring enhancing charge transport, thus achieving a synergistic optimization effect of "one agent with multiple effects".

[0052] 2. BTCA reacts with Pb via the carboxyl group. 2+ Coordination function and its relationship with FA + The hydrogen bonding effect enables dual anchoring of the inorganic framework and organic cations of perovskite, effectively slowing down the crystallization rate, allowing for more complete crystal growth, and resulting in high-quality perovskite films with larger grains, fewer defects, and higher crystallinity.

[0053] 3. The defect state density of BTCA-modified perovskite films is significantly reduced, the carrier lifetime is significantly extended, and nonradiative recombination is effectively suppressed.

[0054] 4. BTCA modification optimizes the energy level arrangement of the perovskite film, reduces the energy level barrier between it and the electron transport layer, and promotes the efficient extraction of photogenerated carriers.

[0055] 5. The BTCA-modified perovskite solar cell achieved a best photoelectric conversion efficiency of 25.2%, an open-circuit voltage of 1.19V, and a fill factor of 83.1%, with all performance indicators significantly better than the unmodified device.

[0056] 6. The method of the present invention is simple and fully compatible with existing solution preparation processes. It does not require additional complex steps and has good prospects for industrial application.

[0057] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent modifications made based on the content of the present invention specification and drawings, or direct or indirect applications in related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for preparing a perovskite thin film, characterized in that, Perovskite films were prepared by adding 4-bromo-2-thiophenic acid to a perovskite precursor solution.

2. The method for preparing perovskite thin films according to claim 1, characterized in that, 4-Bromo-2-thiophenic acid was added to the perovskite precursor solution and dissolved, then spin-coated and annealed to obtain a thin film; subsequently, PEACl solution was spin-coated onto the thin film, and annealed again to obtain a perovskite thin film.

3. The method for preparing perovskite thin films according to claim 1, characterized in that, The perovskite precursor solution is prepared by dissolving PbI2, PbBr2, FAI, CsI, MABr and MACl in a mixed solvent to obtain the perovskite precursor solution.

4. The method for preparing perovskite thin films according to claim 3, characterized in that, The mixed solvent comprises DMF and DMSO in a volume ratio of 3 to 5:

1.

5. The method for preparing perovskite thin films according to claim 2, characterized in that, The specific steps of the spin coating are as follows: first spin coating at 800~1200 rpm for 8~12s, then accelerate to 3800~4200 rpm for 38~42s, and add anti-solvent 3~8s before the end of spin coating.

6. The method for preparing perovskite thin films according to claim 1, characterized in that, The amount of 4-bromo-2-thiophenic acid added to the perovskite precursor solution is 0.05~0.5 mg / mL.

7. A perovskite thin film prepared by the method for preparing perovskite thin films according to any one of claims 1-6, characterized in that, The perovskite thin film has a composition of Cs. 0.05 FA 0.93 MA 0.02 Pb(I 0.98 Br 0.02 3.

8. The application of the perovskite thin film as described in claim 7 in perovskite solar cells, characterized in that, The perovskite solar cell comprises a transparent conductive substrate, a hole transport layer, a perovskite thin film, an electron transport layer, a buffer layer, and a metal electrode, which are stacked sequentially.

9. The application according to claim 8, characterized in that, The hole transport layer is prepared by spin-coating a Me-4PACz solution onto a transparent conductive substrate, followed by annealing and cleaning to obtain the hole transport layer.

10. The application according to claim 8, characterized in that, The electron transport layer is prepared by: using PC 61 BM solution was spin-coated onto a perovskite thin film to obtain an electron transport layer.

Citation Information

Patent Citations

  • Perovskite thin film, perovskite solar cell, preparation method and application

    CN119562746A